Relationship of visceral and subcutaneous adipose depots to markers of arterial injury and inflammation among individuals with HIV. (1st February 2019) - Srinivasa, Suman; Fitch, Kathleen V.; Torriani, Martin; Zanni, Markella V.; Defilippi, Christopher; Christenson, Robert; Maehler, Patrick; Looby, Sara E.; Lo, Janet; Grinspoon, Steven K.
Abstract : Objective: Persons living with HIV (PLWH) well treated on antiretroviral therapies remain at risk for ensuing arterial disease. We investigated the relationship between adipose depots and biomarkers of arterial injury and inflammation to gain insight into the link between body composition and CVD risk. Designs/methods: One hundred and fifty-five HIV-infected and 70 non-HIV infected individuals were well phenotyped for body composition. Adipose depots were assessed via single-slice abdominal computed tomography (CT). Circulating markers of arterial disease and generalized inflammation [lipoprotein-associated phospholipase A2 (LpPLA2), oxidized low-density lipoprotein (oxLDL), high-sensitivity cardiac troponin T (hs-cTnT), high-sensitivity C-reactive protein (hsCRP)] were evaluated. Results: Despite similar BMI and visceral adipose tissue (VAT), HIV-infected individuals had significantly lower subcutaneous adipose tissue [SAT, 199 (126–288) vs. 239 (148–358) cm 2, P = 0.04] than non-HIV infected individuals. Among HIV-infected individuals, reduced SAT inversely correlated with LpPLA2 (ρ = -0.19, P = 0.02) and hs-cTnT (ρ = -0.24, P = 0.004), whereas increased VAT significantly and positively related to LpPLA2 (ρ = 0.25, P = 0.003), oxLDL (ρ = 0.28, P = 0.0005), hs-cTnT (ρ = 0.28, P = 0.0007) and hsCRP (ρ = 0.32, P = < 0.0001). Similar analyses among the non-HIV infected individuals revealed significant relationships between SAT and LpPLA2 (ρ = -0.24, P = 0.05), as well as VAT and LpPLA2 (ρ = 0.37, P = 0.002), oxLDL (ρ = 0.24, P = 0.05) and hsCRP (ρ = 0.29, P = .02). In modelling performed among the HIV group, simultaneously controlling for VAT, SAT, age and relevant HIV-related parameters, reduced SAT was an independent predictor of LpPLA2 ( P = 0.04) and hs-cTnT ( P = 0.005) and increased VAT was an independent predictor of LpPLA2 ( P = 0.001), oxLDL ( P = 0.02), hs-cTnT ( P = 0.04) and hsCRP ( P = 0.04). Conclusion: Fat redistribution phenotypes, characterized by SAT loss and/or VAT accumulation, may be linked to arterial injury and inflammation in HIV.